Dopamine-dependent CB1 receptor dysfunction at corticostriatal synapses in homozygous PINK1 knockout mice. (February 2016) - Madeo, G.; Schirinzi, T.; Maltese, M.; Martella, G.; Rapino, C.; Fezza, F.; Mastrangelo, N.; Bonsi, P.; Maccarrone, M.; Pisani, A.
Abstract: Recessive mutations in the PTEN-induced putative kinase 1 (PINK1) gene cause early-onset Parkinson's disease (PD). We investigated the interaction between endocannabinoid (eCB) and dopaminergic transmission at corticostriatal synapses in PINK1 deficient mice. Whole-cell patch-clamp and conventional recordings of striatal medium spiny neurons (MSNs) were made from slices of PINK1 −/−, heterozygous PINK1 +/− mice and wild-type littermates (PINK1 +/+ ). In PINK1 +/+ mice, CB1 receptor (CB1 R) activation reduced spontaneous excitatory postsynaptic currents (sEPSCs). Likewise, CB1 R agonists (ACEA, WIN55, 212-3 and HU210) induced a dose-dependent reduction of cortically-evoked excitatory postsynaptic potential (eEPSP) amplitude. While CB1 R agonists retained their inhibitory effect in heterozygous PINK1 +/− mice, conversely, in PINK1 −/− mice they failed to modulate sEPSC amplitude. Similarly, CB1 R activation failed to reduce eEPSP amplitude in PINK1 −/− mice. Parallel biochemical measurements revealed no significant difference in the levels of the two main eCBs, 2-arachidonoylglycerol (2-AG) and anandamide (AEA) in PINK1 −/− striata. Similarly, no change was observed in the enzymatic activity of both fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL), responsible for eCB hydrolysis. Instead, a significant reduction of binding ability of CB1 R agonists was found in PINK1 −/− mice. Notably, the CB1 R-dependent inhibition of synaptic activity was restored either by amphetamine or after chronic treatment with the D2 dopamine receptor agonist quinpirole. Additionally, CB1 R binding activity returned to control levels after chronic pretreatment with quinpirole. Consistent with the hypothesis of a close interplay with dopaminergic neurotransmission, our findings show a CB1 R dysfunction at corticostriatal synapses in PINK1 −/−, but not in PINK1 +/− mice, and provide a mechanistic link to the distinct plasticity deficits observed in both genotypes. Highlights: CB1R activation fails to modulate corticostriatal synaptic activity in PINK1−/− mice. Dopaminergic agents rescue normal CB1 R function. Levels of anandamide and 2-AG are unaltered in PINK1 −/− mice. CB1R binding is reduced in PINK1 −/− mice, but is rescued by D2 receptor agonists.